2008
DOI: 10.1097/bpo.0b013e31815a60a6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Evaluation of Clubfoot Correction During Ponseti Treatment

Abstract: Clubfoot correction during serial manipulation can be monitored using sonography. An accurate realignment of the talo-navicular joint can be demonstrated, and presence of spurious correction can be detected early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 24 publications
2
51
0
2
Order By: Relevance
“…At this young age, reliable posttreatment radiographic evaluation is difficult and probably worthless although MRI or US can confirm clinical correction [9,34]. However, imaging confirmation of restoration of normal talonavicular and calcaneocuboid relationships in clinically corrected feet has become increasingly important as spurious correction was reported with an incidence of 15.6% in one study [13,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this young age, reliable posttreatment radiographic evaluation is difficult and probably worthless although MRI or US can confirm clinical correction [9,34]. However, imaging confirmation of restoration of normal talonavicular and calcaneocuboid relationships in clinically corrected feet has become increasingly important as spurious correction was reported with an incidence of 15.6% in one study [13,20].…”
Section: Introductionmentioning
confidence: 99%
“…The one system that has been used before, during, and after treatment on a wider scale than others is the Pirani score [12,13,15,19,21]. In addition to serving as a guide to treatment, this score has the advantage of being quick, reliable, and easy to memorize [15].…”
Section: Introductionmentioning
confidence: 99%
“…These feet which are initially rigid later on showed spurious correction in some cases in study by Desai et al 11 and El-Adwar KL et al 21 Dynamic sonography thus can also guide to the timely need of operative intervention in unresponsive cases. 20 showed that it is necessary to ensure complete sectioning of the tendon, sometimes clinically unapparent connection may remain between the stumps which can theoretically influence the equinus correction.…”
Section: Dynamic Sonographymentioning
confidence: 99%
“…Transducer is placed vertically on the back of foot in midline partly on heel and partly on leg (Figure 7), to assess Tibiocalcaneal relationship, posterior compartment soft tissue thickness and length of tendoachilles ( Figure 8). Posterior projection is also important for evaluation of Achilles tendon percutaneous sectioning 20 and its repair as shown in study by Maranho D et al 20 Apart from these above discussed above Desai et al 11 also measured, talo-cuneiform angle, i.e. angle between a line drawn along the medial border of the talar ossific nucleus and another line along the medial border of the cuneiform at the anterior end of the talar nucleus.…”
Section: Posterior Projectionmentioning
confidence: 99%
See 1 more Smart Citation